Hyssop Plant And Medical Properties - Zakirjonovich, Muradov Rustam; Akmalovna, Nuraliyeva Dilshoda (European Journal of Life Safety and Stability (2660-9630), 2022)
About the biology of hyssop plant, distribution areas, their types, importance in folk medicine, chemical composition, treatment against diseases, mainly the above-ground part is used in modern medicine and medicine, pharmaceutical industry as a remedy for thousands of pains and can be used in diseases. Information about the herbal decoction and tinctures is provided.